INOVASI PENDIDIKAN ISLAM BERBASIS KISAH AL-QUR’AN: MENELAAH INSPIRASI DAN IMPLEMENTASI DALAM PENGEMBANGAN PEMBELAJARAN - Setyaningrum, Putri Nadha; Nida, Sofwatun; Rahmawati3, Nur Widya; Isbah4, Moh Faliqul (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
The Islamic education is closely related to the story of the Qur’an. Much Islamic education is contained in the stories of the Qur’an. The aim this research is to examine story of Qur'an as a source of innovation for Islamic education. This research uses a library method with a qualitative descriptive approach. In this research, it was found that in the stories of Qur'an there is a lot of inspiration to be applied in Islamic education. Integrating Quranic stories into curriculum can enhance students' educational experiences and spiritual growth. There are values ​​of Islamic education in story of Qoran, including value of monotheism education, value of intellectual education, value of moral education, value of sexual education, value of spiritual education and value of democratic education. Methods from Qur'an stories that can be applied in Islamic education, such as the tarhib method, exemplary method, 'ibrah method, through learning method, and others. The implication of this research is Islamic education can be enriched and deepened through a rich exploration the educational values ​​contained in the story of Qoran and what lies behind it. So this has implications for the development and improvement of Islamic education.